Nitrogen dioxide and ammonia gas molecules interaction studies on phosphorene nanosheet — a DFT investigation - Nagarajan, V.; Chandiramouli, R. (Condensed Matter Physics, 2019)
The adsorption behaviour of hazardous gas molecules, namely nitrogen dioxide (NO₂ ) and ammonia (NH₃),
on phosphorene nanosheet (PNS) was explored by means of ab initio technique. To improve the structural
solidity of pristine PNS, we have introduced the passivation of hydrogen and fluorine at the terminated edge.
The structural solidity of both hydrogen and fluorine passivated PNS is verified in terms of formation energy.
The main objective of this research work is to probe NO₂ and NH₃ gases using PNS as a base sensing material.
The adsorption of various preferential adsorption sites of these gas molecules is studied in accordance with
the average HOMO-LUMO gap changes, natural-bond-orbital (NBO) charge transfer, HOMO-LUMO gap, and
adsorption energy. Notably, the negative value of adsorption energy is found upon the adsorption of NO₂ and
NH₃ on PNS and it is in the range of −1.36 to −2.45 eV. The findings of the present research work recommend
that the hydrogenated and fluorinated PNS can be effectively used as a chemical sensor against NO₂ and NH₃
molecules. Адсорбцiйнi характеристики небезпечних газових молекул, а саме двоокису вуглецю (NO₂) та амонiяку
(NH₃), на фосфореновому нанолистi дослiджено з допомогою ab initio методики. Для покращення структурної мiцностi первинного нанолиста, ми здiйснили пасивацiю водню i фтору на кiнцевому ребрi. Структурну мiцнiсть пасивованого воднем i фтором фосфоренового листа перевiрено з огляду на формування
енергiї. Основною метою даної роботи є дослiдити гази NO₂ i NH₃, використовуючи фосфореновий нанолист в якостi базового сенсорного матерiалу. Адсорбцiю рiзноманiтних селективних адсобцiйних вузлiв
цих газових молекул дослiджено у вiдповiдностi до змiн середньої HOMO-LUMO щiлини, перенесення заряду натуральний-зв’язок-орбiталь (NBO), HOMO-LUMO щiлини та енергiї адсорбцiї. Варто вiдзначити, що
знайдено вiд’ємне значення енергiї адсорбцiї пiсля адсорбцiї NO₂ i NH₃на фосфореновому нанолистi, i
воно знаходиться в дiапазонi вiд −1.36 до −2.45 еВ. Результати даної роботи доводять, що гiдрогенiзований i фторований фосфореновий нанолист можна ефективно використовувати в якостi хiмiчного сенсора
молекул NO₂ i NH₃.